2019
DOI: 10.1016/j.celrep.2019.07.058
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 Inhibition Promotes Epithelial Differentiation through Derepression of Fate-Determining Transcription Factors

Abstract: Highlights d LSD1 represses master epidermal transcription factors that promote differentiation d LSD1 inhibition activates the epidermal differentiation transcriptional program d LSD1 inhibition represses invasion in a model of cutaneous squamous cell carcinoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 75 publications
1
54
2
Order By: Relevance
“…Here, we find that LSD1 is required for postnatal intestinal epithelial maturation. The role we find for LSD1 in suppressing fetal/neonatal genes is near opposite of what recently was found in skin ( 39 ). In skin epithelium, inhibition of LSD1 leads to the increase of fate-determining transcription factors and subsequent differentiation, and this enhanced differentiation led to inhibition of skin cancer progression ( 39 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Here, we find that LSD1 is required for postnatal intestinal epithelial maturation. The role we find for LSD1 in suppressing fetal/neonatal genes is near opposite of what recently was found in skin ( 39 ). In skin epithelium, inhibition of LSD1 leads to the increase of fate-determining transcription factors and subsequent differentiation, and this enhanced differentiation led to inhibition of skin cancer progression ( 39 ).…”
Section: Discussioncontrasting
confidence: 99%
“…KDM1A is overexpressed in numerous epithelial cancers and promotes proliferation, migration and invasion. Egolf et al [65] reported that its downstream targets were involved in epidermal differentiation and cornification processes. Kong et al [66] indicated that treatment with KDM1A inhibitor (2-PCPA) reduced tumour NSCLC cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of LSD1 leads to an activation of a neuronal differentiation program, driving MCC cells toward a normal Merkel cell fate and inducing cell cycle arrest and cell death. We show that LSD1 inhibitors lead to the disruption of the LSD1‐CoREST complex and the displacement and eventual degradation of the subunit HMG20B, similar to SNAG domain‐containing proteins that get released from the LSD1‐CoREST complex upon LSD1 inhibition in other cellular contexts (Ferrari‐Amorotti et al , 2013; Maiques‐Diaz et al , 2018; Egolf et al , 2019). Notably, HMG20B has previously been implicated in the repression of neuronal lineage‐specific genes (Hakimi et al , 2002; Ceballos‐Chávez et al , 2012).…”
Section: Discussionmentioning
confidence: 56%
“…Putting our findings in MCC in the broader context of studies investigating LSD1i treatment in other cancers, such as AMLs (Schenk et al , 2012; Somervaille et al , 2016; Fang et al , 2019; Cai et al , 2020), SCLC (Mohammad et al , 2015; Augert et al , 2019), prostate cancer (Sehrawat et al , 2018), and cutaneous squamous cell carcinoma (Egolf et al , 2019), it appears that in certain cellular lineages, the neuroendocrine lineage among them, LSD1 is a gate‐keeper of lineage plasticity. Inhibition of LSD1 may therefore represent a tractable entry point for differentiation therapies of solid cancers.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation